(untitled) (Journal of Nobel Medical College, 2014)
The prime role of the hydrochloric acid secreted by the parietal cells of the stomach is to assist in digestion of food .The another important role of it is to assist in immunity. The presence and secretion of the hydrochloric acid is a part of innate immunity that fights against the pathogens that enter our body through oral route. However if a person drinks fluids while eating food, the hydrochloric acid whose pH is 2-3, is greatly diluted and as a result the acid cannot effectively prevent the invasion of the GI tract by pathogens that are present in our food and water .This study reveals that those subjects who do not drink water while eating food but drink it after one hour of consumption of food are less likely to be infected with pathogens through GI tracts. Whereas those people who drink water while taking food are more prone to be infected by the pathogens. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10056 Journal of Nobel Medical College Vol.3(1) 2014; 58-61